EFFECTIVENESS OF SQUID ATTRACTOR MADE FROM FIBER BIOCOMPOSITE (ARENGA PINNATA MERR) IN LEMBEH STRAIT WATERS BITUNG CITY NORTH SULAWESI - Adi Saputra; Danu Sudrajat; Mulyono S. Baskoro; Noriko Runtu (Universitas Mataram, 2024)
One effort to increase squid resources in aquatic areas is by installing a squid attractor, which is used as a place for squid to release their eggs. The aim of installing a squid attractor is to create an artificial coral reef, so the construction of a squid attractor should follow the requirements for artificial coral reefs. This artificial coral reef will later become a new ecosystem in a body of water. This research aims to determine the effectiveness of a squid attractor made from palm fiber biocomposite. The research method uses a direct-trial experimental method. Data analysis uses descriptive analysis and analysis of the effectiveness of squid attractors. The research findings indicate that biocomposite attractors made from palm fiber are categorized as effective based on the number of attractors successfully attracting squid eggs. The squid species (Sepia, sp.) adhered their eggs to these attractors. The effectiveness analysis calculations show that the obtained effectiveness rate is 60%. Apart from that, this attractor made from palm fiber biocomposite effectively forms new ecosystems. This is indicated by the significant biofouling growth in the attractor made from palm fiber biocomposite. Apart from that, a fish association is around installing this squid attractor made from palm fiber biocomposite.